X-Ray Photoelectron Spectroscopy Studies on Activated Carbon Prepared From Rind of Citrus nobilis - VENKATESWARA RAO, K.V.; KISHORE, G.; SOMASEKHARA RAO, KAZA; VANI, K.N.K.; NAGESWARA RAO, M.; HANUNTHA RAO, Y. (Asian Journal of Chemistry, 2010)
The rind of Citrus nobilis is waste biomass material. The raw material was carbonized in the inert gas atmosphere and the resulting carbon was activated with 0.1 N nitric acid. The surface studies were made using X-ray photoelectron spectroscopy analysis. The results indicate the concentration of surface oxides. The prepared carbon was used for defluoridation. X-Ray photoelectron spectroscopy studies indicate that the fluoride is adsorbed on activated carbon.